Case Report: Ensartinib for gastric epithelioid inflammatory myofibrosarcoma with STRN-ALK fusion - Li, XiaoQing; Zheng, JingFan; Li, XinYi; Chen, YuYu; Liu, Kang; Li, FangChao; Lu, Zhong (Frontiers in Oncology, 2023)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is a highly aggressive malignant subtype of inflammatory myofibroblastoma (IMT) associated with poor prognosis. IMT can occur in various parts of the body, most frequently in the lungs, followed by the mesentery, omentum, retroperitoneum, and pelvis, among other areas; however, it is exceptionally rare in the stomach. Anaplastic lymphoma kinase (ALK) is a critical driver of lung cancer development and is currently the “gold standard” target for non-small cell lung cancer treatment. However, there are few reports on the use of ALK inhibitors for EIMS, necessitating further investigation. A male patient with postoperative inflammatory myofibroblastic sarcoma of the stomach received postoperative chemotherapy and had a stable outcome. However, a repeat CT scan performed 11 months later revealed disease progression. The patient later underwent immunohistochemistry testing that indicated ALK positivity, and next-generation sequencing revealed STRN-ALK fusion. Ensartinib 225 mg qd was administered as recommended, and the patient experienced only mild pruritus and no adverse effects such as rash. Eight months after CT follow-up, the patient's subseptal soft tissue nodules had decreased, and the outcome was assessed as a partial response. The findings of this case report introduce a novel strategy for treating ALK-positive EIMS that utilizes ensartinib, a drug with previously demonstrated success in the treatment of ALK-positive cancer.